DYNAMIC LOAD ON THE RAILS OF THE RAILWAY TRACK IN PLACES OF THEIR JOINING - Dzhus, V. S.; Kulichenko, O. Ya. (Science and Transport Progress, 2007)
The authors have proposed rather simple differential method of calculating the coefficient of shove depending on the moving speed of railway carriage and the ratio of inflexibility of its wheel suspension.